1986
DOI: 10.2307/1939812
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Habitat Manipulations on Interactions Between Cutthroat Trout and Invertebrate Drift

Abstract: The objectives of this study were to examine the interactions of the riparian setting (logged vs. forested) and prey availability on the prey capture efficiency and growth of cutthroat trout, and to determine if the riparian setting influences the impact of trout predation on drift composition. Short-term relative growth rates of cutthroat trout, experimentally confined in stream pools, were greater in a logged than in a forested section of stream. Differences in growth rates were attributed to differences amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
128
0
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(141 citation statements)
references
References 41 publications
12
128
0
1
Order By: Relevance
“…Secondly, the negative growth effect we observed occurred at relatively low fish densities (;0.02-0.9 fish/m 2 ), a pattern observed in other studies (see Jenkins et al 1999). Thirdly, the positive effect of prey availability (in this case, adult Diptera drift) on coho growth confirmed experimental results, and results from similar investigations (Wilzbach et al 1986, Rosenfeld et al 2005, Ward et al 2009). Fourthly, coho in the field showed a strong preference for chironomid pupae and adults relative to their availability, a relationship also observed in the experiment.…”
Section: Field Studysupporting
confidence: 89%
“…Secondly, the negative growth effect we observed occurred at relatively low fish densities (;0.02-0.9 fish/m 2 ), a pattern observed in other studies (see Jenkins et al 1999). Thirdly, the positive effect of prey availability (in this case, adult Diptera drift) on coho growth confirmed experimental results, and results from similar investigations (Wilzbach et al 1986, Rosenfeld et al 2005, Ward et al 2009). Fourthly, coho in the field showed a strong preference for chironomid pupae and adults relative to their availability, a relationship also observed in the experiment.…”
Section: Field Studysupporting
confidence: 89%
“…However, in most field studies where confounding factors are numerous, it has been found that the presence of cover has no (SAUNDERS and SMITH, 1962;FAUSCH and NORTHCOTE, 1992;FAUSCH et al, 1995;FLEBBE and DOLLOFF, 1995;GOWAN and FAUSCH, 1996;HARVEY, 1998) or even a negative effect (WILZBACH et al, 1986) on growth although increased growth rates are sometimes attributed to the presence of rootwad cover (NIELSEN, 1992) or riparian cover (VILA-GISPERT et al, 2000). Results obtained in laboratory experiments are also equivocal due to difficulties in defining working hypotheses and to methodological problems (e.g.…”
Section: Effects Of Cover Structures On Biological Productivitymentioning
confidence: 99%
“…Overall, numerous studies have reported that structural complexity in macrophytes (DIEHL, 1988;SAVINO et al, 1992), woody debris (EVERETT and RUIZ, 1993), and substratum (POWER, 1992;BECHARA et al, 1993) may decrease the effectiveness of fish predation on macroinvertebrates. By impeding their visual field, shade may drastically limit the feeding efficiency of drift-feeders (WILZBACH et al, 1986;O'BRIEN and SHOWALTER, 1993) that may benefit far more from cover structures by taking positions directly downstream from these structures (NIELSEN, 1992). At a higher spatial scale, riparian cover may both greatly reduce autochthonous production of a stream reach thus negatively impacting fish growth, but also provide terrestrial invertebrates which may constitute a large part, at least seasonally, of the diets of some species (MASON and MACDONALD, 1982;COLLARES-PEREIRA et al, 1995;BRIDCUT, 2000;KAWAGUCHI and NAKANO, 2001).…”
Section: Foragingmentioning
confidence: 99%
See 1 more Smart Citation
“…As species are not independent entities -taking into account that biotic and abiotic connections are essential for the maintenance of integrity of the lotic systems -the quantification of predator impact on the abundance of prey has been studied by some authors (Thorp and Bergey, 1981;Flecker and Allan, 1984;Wilzbach et al, 1986;Rahel and Stein, 1988;Soluk and Collins, 1988;Lancaster, 1990;Cooper et al, 1990;Hanson et al, 1990;Flecker, 1992;Prejs and Prejs, 1992;Bechara et al, 1993;Lancaster andRobertson, 1995, McIntosh andTownsend, 1996;Dahl, 1998;Billy and Usseglio-Polatera, 2002). Amongst the factors that influence the response of prey to predator are: a) predator feeding characteristics, being that not all the taxa are affected (Billy and Usseglio-Polatera, 2002); b) size of prey and substrate type, presenting a higher or lower degree of shelter sites (Bechara et al, 1993) and c) types of habitats, which may have a differentiated effect, taking into consideration that in habitats made up of riffles and rapids, colonization rates are higher than in pools, causing a lower response to predators (Cooper et al, 1990).…”
Section: Introductionmentioning
confidence: 99%